First experience of using two-stage resection of the liver (split in situ) in patients with extensive metastasis in the Ural region - D. V. Chaichenko (Sibirskij Onkologičeskij Žurnal, 2016)
The first experience of using the technique of two-stage resection of the liver (split in situ) in patients with extensive metastasis has been presented. This technique allows the surgeon to perform operation in cases with extensive metastasis reducing the incidence of postoperative hepatic failure, which is one of the main limited factors when choosing the extent of the liver resection.